Wearable Potentiometric Ion Patch for On-Body Electrolyte Monitoring in Sweat: Toward a Validation Strategy to Ensure Physiological Relevance - Parrilla, Marc; Ortiz-Gómez, Inmaculada; Cánovas, Rocío; Salinas-Castillo, Alfonso; Cuartero, María; Crespo, Gastón A (Analytical chemistry (Washington), 2019)
Herein, the reproducibility and a double validation of on-body measurements provided by new wearable potentiometric ion sensors (WPISs) is presented. Sweat collected during sport practice was first analyzed using the developed device, the pH-meter, and ion chromatography (IC) prior to on-body measurements (off-site validation). Subsequently, the accuracy of on-body measurements accomplished by the WPISs was evaluated by comparison with pH-meter readings and IC after collecting sweat (every 10-12.5 min) during sport practice. The developed device contains sensors for pH, Cl , K , and Na that are embedded in a flexible sampling cell for sweat analysis. The electrode array was fabricated employing MWCNTs (as an ion-to-electron transducer) and stretchable materials that have been exhaustively characterized in terms of analytical performance, presenting Nernstian slopes within the expected physiological range of each ion analyte (Cl , 10-100 mM; K , 10-10 mM; and Na , 10-100 mM and pH, 4.5-7.5), drift suitable for midterm exercise practice (0.3 ± 0.2 mV h ), fast response time, adequate selectivity for sweat measurements, and excellent reversibility. Besides that, the designed sampling cell avoids any sweat contamination and evaporation issues while supplying a passive sweat flow encompassing specifically the individual's perspiration. The interpretation of ion concentration profiles may permit the identification of personal dynamic patterns in sweat composition while practicing sport.